The Release of Curcumin from β-TCP/SiO₂/Curcumin Composites in a Ringer’s Lactate Solution - Tri Windarti; Ngadiwiyana Ngadiwiyana; Fadila Fibriani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Osteoporosis is characterized by bone deterioration caused by high levels of reactive oxygen species (ROS), which inhibit osteoblast activity and lead to a decrease in bone density. Adding curcumin, a natural antioxidant, to calcium phosphate cement (CPC) enhances its function beyond simply increasing bone density. In this study, CPC was prepared from a β-tricalcium phosphate (β-TCP, β-Ca3(PO4)2) composite with curcumin. To enhance the interaction between β- TCP and curcumin, silicon dioxide (SiO2) was added. β-TCP was synthesized by the sol-gel method, with SiO2 content ranging from 1.6 to 8.3%. CPC preparation was carried out using a 2.5% Na2HPO4 solution. The release of curcumin in a Ringer’s lactate solution was studied in relation to the role of SiO2. The UV-Vis spectral intensity of the remaining Ringer’s lactate solution after soaking decreased as the SiO2 content increased. Results from a five-day soaking period showed that β-TCP did not transform into hydroxyapatite, but rather experienced a decrease in crystallinity and average crystal size from 96.175% to 25.524% and from 58.335 nm to 39.474 nm, respectively. Therefore, it can be predicted that CPC can maintain the presence of curcumin in a physiological environment.